ChemInform Abstract: Regioselective Electrophilic Fluorination of Rationally Designed Imidazole Derivatives. Issue 26 (June 2016) - Albertshofer, Klaus; Mani, Neelakandha S.
Abstract: Lithium tetramethylpiperidide is found to efficiently promote the regioselective fluorination of N‐protected 2‐substituted imidazoles (I) and (IV) to give the products regioselectively.